Einstein's greatest mistake : a biography - Bodanis, David (Houghton Mifflin Harcourt, 2016)
A portrait of Albert Einstein shares critical insights into both the genius and hubris of modern physics, linking Einstein's popular downfall through the final decades of his life to the same imagination and self-confidence that ignited his early successes.